Biomarker screening in children and adolescents reveals that CUB domain-containing protein 1 is associated with obesity and that hepatocyte growth factor is associated with weight gain. (May 2023) - Manell, Hannes; Shen, Qiujin; Chowdhury, Azazul; Roomp, Kirsten; Ciba, Iris; Weghuber, Daniel; Kamali-Moghaddam, Masood; Bergsten, Peter; Forslund, Anders
Abstract: Background: Low-grade inflammation is a hallmark of obesity, hyperinsulinemia and type 2 diabetes (T2D), although its role in adolescent T2D and impaired glucose tolerance (IGT) is less known. Objectives: To identify novel inflammatory protein biomarkers related to childhood obesity, IGT, hyperinsulinemia and hyperglucagonemia and increase in age-adjusted BMI over time. Methods: Children and adolescents with obesity (n = 137; eight with T2D, 45 with IGT, 84 with normal glucose tolerance (NGT)), and with normal weight (n = 34) were included. Study subjects were 5–18 years old. In the obesity group the majority were above the 99th BMI percentile. Protein biomarker identification in plasma was performed using proximity extension assay with a 92-plex inflammation-related protein panel. The biomarkers were tested for their association with childhood obesity, IGT, hyperinsulinemia, hyperglucagonemia by t-tests and with increased BMI SDS by linear regression. Results: Six protein biomarkers not previously studied in childhood obesity were elevated in pediatric obesity, among these CUB domain containing protein 1 (CDCP1). Plasma TNF-related Weak Inducer of Apoptosis (TWEAK) was lower in the IGT than in the NGT group. Five protein biomarkers were elevated in hyperinsulinemia and two were elevated in hyperglucagonemia. A high baseline HGF was associated with increased BMI SDS after a follow-up period of on average 1.8 years (B = 0.008, 95% CI 0.005–0.011). Conclusions: Six protein biomarkers not previously described in childhood obesity were identified, among these CDCP-1. A high HGF is associated with increased BMI over time in children and adolescents with obesity. Highlights: CDCP1 is a novel biomarker of obesity. HGF is associated with weight gain in childhood obesity. Six protein biomarkers novel to childhood obesity are identified